The McGraw-Hill Education handbook of English grammar and usage - Lester, Mark; Beason, Larry (New York : McGraw-Hill Education, 2019)
Reviews the rules of English grammar, covering such topics as verb forms, subject-verb agreement, punctuation, capitalization, parallelism, who versus whom, and etiquette for digital communication.
Part I: Grammar 101. Parts of speech ; Basic phrases ; Sentences and clauses ; Verb forms ; Verbals -- Part II: How to find and correct mistakes. Writing complete sentences ; Subject-verb agreement ; Pronoun problems ; Verb problems ; Modification ; Commas ; Apostrophes ; Semicolons and colons ; Quotation marks ; Dashes, hyphens, and other punctuation ; Capitalization ; Parallelism ; Grammar etiquette for digital communication -- Appendix A: Homophone misspellings and commonly confused word.
Includes index.
PB
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: English language -- Grammar -- Handbooks, manuals, etc; English language -- Usage -- Handbooks, manuals, etc; LANGUAGE ARTS & DISCIPLINES / Grammar & Punctuation; English language -- Grammar; English language -- Usage; Handbooks and manuals; Handbooks and manuals